2010
DOI: 10.1111/j.1420-9101.2010.02109.x
|View full text |Cite
|
Sign up to set email alerts
|

The dual function of barred plumage in birds: camouflage and communication

Abstract: A commonly held principle in visual ecology is that communication compromises camouflage: while visual signals are often conspicuous, camouflage provides concealment. However, some traits may have evolved for communication and camouflage simultaneously, thereby overcoming this functional compromise. Visual patterns generally provide camouflage, but it was suggested that a particular type of visual pattern – avian barred plumage – could also be a signal of individual quality. Here, we test if the evolution of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 27 publications
2
53
0
Order By: Relevance
“…Similar plumage patterns have evolved in many distantly and closely related species of birds [9, 11, 43]. We demonstrated that plumage pattern evolution follows sequential steps that is congruent with developmental constraint.…”
Section: Discussionsupporting
confidence: 63%
“…Similar plumage patterns have evolved in many distantly and closely related species of birds [9, 11, 43]. We demonstrated that plumage pattern evolution follows sequential steps that is congruent with developmental constraint.…”
Section: Discussionsupporting
confidence: 63%
“…Previous analyses of only barred plumage in cuckoos have found this to be a derived trait that most likely arose after the evolution of parasitism (Krüger et al, 2007). Analyses with all avian families have also shown that sexual selection may play a role in the evolution of barred plumage (Gluckman and Cardoso, 2010), but this does not seem to be the case for cuckoos (Krüger et al, 2007). Our results show that Fig.…”
Section: Discussionmentioning
confidence: 42%
“…1), 2011). In birds, classical functions assigned to melanin-based phenotypes are those related to individual recognition (Dale et al 2001), thermoregulation (e.g., Sirkiä et al 2010), camouflage (Galeotti andRubolini 2004, Gluckman andCardoso 2010), photoprotection (Hadley 1972), and signaling (e.g., Senar and Camerino 1998).…”
mentioning
confidence: 99%